2015
DOI: 10.4018/978-1-4666-8490-4.ch012
|View full text |Cite
|
Sign up to set email alerts
|

An Implementation of a Complete Methodology for Wind Energy Structures Health Monitoring

Abstract: In this chapter a complete methodology for a SHM damage detection solution is explained, and how this is validated in a laboratory tower model. Several methodologies are proposed for the typical process of SHM. Starting with sensor placement (the best possible sensor locations are found), selecting the more representative data, classifying the different environmental and operational conditions, applying a damage detection methodology, including sensor fault detection. The paradigm of damage detection can be ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The results show that the damage detection and damage diagnosis results are promising, as they achieved great performance on different structural state samples. Finally, to thoroughly test the functional characteristics of the algorithm, a comparison is made with four other methodologies given in [31], [32], [13], and [12] that use the same laboratory structure. The first methodology, given in [31], is based on principal component analysis and support vector machines.…”
Section: Predicted Classmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that the damage detection and damage diagnosis results are promising, as they achieved great performance on different structural state samples. Finally, to thoroughly test the functional characteristics of the algorithm, a comparison is made with four other methodologies given in [31], [32], [13], and [12] that use the same laboratory structure. The first methodology, given in [31], is based on principal component analysis and support vector machines.…”
Section: Predicted Classmentioning
confidence: 99%
“…The first methodology, given in [31], is based on principal component analysis and support vector machines. The second methodology, given in [32] (page 67), is based on the well-known damage indicators: covariance matrix estimate and scalar covariance. The third methodology, given in [13], is based on machine learning methods and the fractal dimension feature.…”
Section: Predicted Classmentioning
confidence: 99%
“…The structure of a small-scale wind-turbine foundation is used to validate the damage detection and localization methodology developed in this study. This benchmark structure, based on the one designed by Zugasti [ 35 ], was considered by Hoxha et al [ 36 ], Vidal et al [ 7 ], and Puruncajas et al [ 13 ] to validate different approaches for structural damage detection and classification experimentally. The benchmark structure—placed in the CoDAlab laboratory (Escola d’Enginyeria de Barcelona Est, Universitat Politècnica de Catalunya, Barcelona, Spain)—is shown in Figure 3 a; it is composed of three parts: (i) the nacelle on the top, (ii) tower in the middle, and (iii) jacket on the bottom.…”
Section: Data Preprocessing: Training Data Preparationmentioning
confidence: 99%
“…A 5 mm crack was introduced at four different bars located in the jacket structure, one at a time. It can be said that the 5 mm crack damage is small for this structure [ 35 ] and therefore hard to detect. Summarizing, four different damage scenarios are considered in this study, as shown in Figure 3 b.…”
Section: Data Preprocessing: Training Data Preparationmentioning
confidence: 99%
See 1 more Smart Citation